2021
DOI: 10.3390/molecules26237391
|View full text |Cite
|
Sign up to set email alerts
|

Novel β-Cyclodextrin and Catnip Essential Oil Inclusion Complex and Its Tick Repellent Properties

Abstract: Cyclodextrin inclusion complexes have been successfully used to encapsulate essential oils, improving their physicochemical properties and pharmacological effects. Besides being well-known for its effects on cats and other felines, catnip (Nepeta cataria) essential oil demonstrates repellency against blood-feeding pests such as mosquitoes. This study evaluates the tick repellency of catnip oil alone and encapsulated in β-cyclodextrin, prepared using the co-precipitation method at a 1:1 molar ratio. The physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…Therefore, in pharmaceutical, agriculture, food, and cosmetic industries, β-CD is utilized to manufacture inclusion complexes [13][14][15][16][17]. Several studies have demonstrated the process and performance of inclusion complexes based on β-CD and various essential oil [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in pharmaceutical, agriculture, food, and cosmetic industries, β-CD is utilized to manufacture inclusion complexes [13][14][15][16][17]. Several studies have demonstrated the process and performance of inclusion complexes based on β-CD and various essential oil [18][19][20].…”
Section: Introductionmentioning
confidence: 99%